2013
DOI: 10.1111/nep.12018
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of mesenchymal stem/stromal cells therapy for impaired renal function in small animal models

Abstract: The present meta-analysis confirmed that MSC therapy could improve impaired renal function. MSCs might get obvious effect in the early stage of renal injuries after arterial delivery. Further, this meta-analysis may provide important clues for animal experiments even for human clinical trials in MSC studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 30 publications
4
76
0
1
Order By: Relevance
“…Literature informs, for example, that stem/progenitor cells can be principally administered via the arterial or venous vessel system, by punctual injections into diseased parenchyma or by seeding in the space left between the organ capsule and the outer parenchyma [4,5]. The various results illustrate that irrespective of applied implantation technique the expectations have not been achieved yet.…”
Section: Introductionmentioning
confidence: 99%
“…Literature informs, for example, that stem/progenitor cells can be principally administered via the arterial or venous vessel system, by punctual injections into diseased parenchyma or by seeding in the space left between the organ capsule and the outer parenchyma [4,5]. The various results illustrate that irrespective of applied implantation technique the expectations have not been achieved yet.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Wang et al [67] showed that transplanted BM-MSCs improved a wide variety of kidney disorders, from AKI to CKD, which further indicates that these cells are renoprotective after arterial delivery during the early stages of renal injury.…”
Section: Cell-based Approach: Cell Therapymentioning
confidence: 95%
“…In a systematic meta-analysis of 21 of these studies [3], the authors found a consistent reduction in serum creatinine (sCr) in MSC-treated animals versus controls. The studies differed in terms of time point and dose of MSC administered, time point of sCr measurement, route of MSC delivery, type of kidney injury and animal used (mice vs. rats).…”
Section: Mechanisms Of Msc Protection Against Acute Kidney Injurymentioning
confidence: 99%